Intrinsic Cultural Factors That Helped Vietnam Overcome the COVID-19 Pandemic Compared with Other Countries. - Ngoc Cindy Pham; Yuanqing Li; Claudio Schapsis; Tofazzal Hossain; Huan Henry Pham; Dov Fischer; Jun Yang (ACHSM, 2020)
The Coronavirus Disease 2019 (COVID-19) pandemic emerged in Wuhan, China, spread nationwide and then onto many other countries between December 2019 and early 2020. The implementation of strict quarantine measures in Vietnam has kept a large number of people in isolation and has eventually put the disease under control. Social and physical distancing turned to be an efficient way of slowing the spread of disease and stopping chains of transmission of COVID-19 as well as preventing new ones from appearing (World Health Organization, 2020). Analyzing the World Health Organization (WHO) data, we could see a clear difference in the reported numbers between Vietnam, a developing country, and the USA, one of the leading developed countries in the western hemisphere. We tried to address the question if there are factors that helped local governments to implement helpful rules. We argue that Eastern Asian cultural traits played a role in reducing the spread of COVID-19. We recommend to take this commentary paper, and further research those cultural factors that positively affected the slowdown of the spread of the COVID-19 pandemic in Vietnam.